2019
DOI: 10.5004/dwt.2019.24176
|View full text |Cite
|
Sign up to set email alerts
|

Improved sludge dewaterability by combining SDS pre-treatment conditioning with PDMDAAC flocculation

Abstract: Wastewater treatment generates considerable amounts of sludge. Reducing sludge volume by dewatering is an important part of many wastewater treatment processes. We investigated the effects of a combination of sodium dodecyl sulfate (SDS) and polydimethyldiallylammonium chloride (PDMDAAC) on anaerobically digested sludge dewaterability. Capillary suction time (CST) and specific resistance to filtration (SRF) were measured as indicators of sludge dewaterability. Extracellular polymeric substances (EPS) content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…With a wide range of prospective applications, particularly in the domains of petrochemicals, water treatment, personal care, biomedicine, and electrochemical materials, its homopolymers and copolymers occupy a highly special and significant position for study. [1][2][3][4][5][6][7][8][9] There is still much room for improvement in their applicable applications, particularly those involving aromatic lipophilic applications like petroleum extraction and wastewater treatment for printing and dyeing, as DMDAAC-based polymers frequently struggle with weak affinities to aliphatic substances. Currently, there are a large number of applications for lipophilicity based on aromatic rings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a wide range of prospective applications, particularly in the domains of petrochemicals, water treatment, personal care, biomedicine, and electrochemical materials, its homopolymers and copolymers occupy a highly special and significant position for study. [1][2][3][4][5][6][7][8][9] There is still much room for improvement in their applicable applications, particularly those involving aromatic lipophilic applications like petroleum extraction and wastewater treatment for printing and dyeing, as DMDAAC-based polymers frequently struggle with weak affinities to aliphatic substances. Currently, there are a large number of applications for lipophilicity based on aromatic rings.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic monomer of diallyl quaternary ammonium salt cationic polymers, a family of water‐soluble organic polymers with significant features, is dimethyl diallyl ammonium chloride (DMDAAC). With a wide range of prospective applications, particularly in the domains of petrochemicals, water treatment, personal care, biomedicine, and electrochemical materials, its homopolymers and copolymers occupy a highly special and significant position for study 1–9 . There is still much room for improvement in their applicable applications, particularly those involving aromatic lipophilic applications like petroleum extraction and wastewater treatment for printing and dyeing, as DMDAAC‐based polymers frequently struggle with weak affinities to aliphatic substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-soluble cationic polyelectrolytes are a kind of important polymers, among which the study of homopolymers and copolymers of dimethyl diallyl ammonium chloride (DMDAAC) occupies a very unique and important position. They have been widely used in water treatment, petroleum exploitation, textile printing, dyeing, the daily chemical industry, the pharmaceutical chemical industry, electrochemical materials, electronic sensors, and other fields [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In addition, to improve the relative molecular weight of DMDAAC-based polymers to form products with serial cationicity and relative molecular weight, in recent years, it was found that the group structure of quaternary ammonium nitrogen is directly related to its mode of action and efficiency at the phase interface, especially in some lipophilic application fields.…”
Section: Introductionmentioning
confidence: 99%